Comparative evaluation of use of diode laser and electrode with and without two dentinal tubule occluding agents in the management of dentinal hypersensitivity: An experimental in vitro study - Chitra Laxmikant Patil; Rajesh Prabhakar Gaikwad (Wolters Kluwer Medknow Publications, 2020)
Background: The present study aims to assess area of open dentinal tubules by use of diode laser and electrode alone and in combination with hydroxyapatite powder and strontium chloride powder by using the scanning electron microscope (SEM). Materials and Methods: A double-blinded study was carried out with 30 extracted teeth with no carious lesion or restored teeth were selected and grouped randomly as Group A - diode laser, Group B - electrode application, Group C - hydroxyapatite powder plus diode laser, Group D - hydroxyapatite powder plus electrode application, Group E - strontium chloride powder plus diode laser, and Group F - strontium chloride powder plus electrode application. All the samples were made by preparing a notch of 2 mm measured with UNC-15 probe at cementoenamel junction using a diamond cylindrical bur at high speed. The teeth were then washed with distilled water and stored in solution containing 2.5% glutaraldehyde solution in 0.1 M sodium phosphate buffer for 24 h. The samples were treated as mentioned in above said groups and were viewed under SEM the degree of occlusion of the dentinal tubules were quantified using an image analyzer. Results: Highest number of open dentinal tubules was found with Group B, that is, electrode application, whereas Group C, that is, hydroxyapatite powder plus diode laser showed highest occluded tubules. One-way ANOVA showed statistically significant difference across all the groups (P = 0.000); further, intergroup comparison with Tukey's test showed better tubular occlusion with Group C. Conclusion: The SEM results showed highest tubular occlusion with hydroxyapatite powder plus diode laser and least with electrode.